Head and neck cancer – emerging targeted therapies - Abouelkheer, Yasser; Bhatia, Aarti (Frontiers in Oncology, 2025)
Systemic therapy remains the cornerstone of treatment for recurrent and metastatic (R/M) head and neck squamous cell cancers (HNSCC). However, there is a dearth of effective treatments beyond platinum combinations, anti-programmed death-1 (PD-1) agents and the epidermal growth factor receptor (EGFR)-targeting monoclonal antibody cetuximab. Recent years have seen several exciting new agents being tested in clinical trials. These are designed to target alternate oncogenic signaling pathways and have novel mechanistic compositions, including bi-specific antibodies and antibody-drug conjugates. This review will delve into the clinical limitations of currently approved systemic therapies, explore newer agents in development and highlight ongoing clinical trials using targeted therapies in this disease.